Isolated systolic hypertension in the young: a position paper endorsed by the European Society of Hypertension. Issue 6 (June 2018) - Palatini, Paolo; Rosei, Enrico Agabiti; Avolio, Alberto; Bilo, Gregorz; Casiglia, Edoardo; Ghiadoni, Lorenzo; Giannattasio, Cristina; Grassi, Guido; Jelakovich, Bojan; Julius, Stevo; Mancia, Giuseppe; McEniery, Carmel M.; et al.
Abstract : N/A: Whether isolated systolic hypertension in the young (ISHY) implies a worse outcome and needs antihypertensive treatment is still a matter for dispute. ISHY is thought to have different mechanisms than systolic hypertension in the elderly. However, findings from previous studies have provided inconsistent results. From the analysis of the literature, two main lines of research and conceptualization have emerged. Simultaneous assessment of peripheral and central blood pressure led to the identification of a condition called pseudo or spurious hypertension, which was considered an innocent condition. However, an increase in pulse wave velocity has been found by some authors in about 20% of the individuals with ISHY. In addition, obesity and metabolic disturbances have often been documented to be associated with ISHY both in children and young adults. The first aspect to consider whenever evaluating a person with ISHY is the possible presence of white-coat hypertension, which has been frequently found in this condition. In addition, assessment of central blood pressure is useful for identifying ISHY patients whose central blood pressure is normal. ISHY is infrequently mentioned in the guidelines on diagnosis and treatment of hypertension. According to the 2013 European Guidelines on the management of hypertension, people with ISHY should be followed carefully, modifying risk factors by lifestyle changes and avoiding antihypertensive drugs. Only future clinical trials will elucidate if a benefit can be achieved with pharmacological treatment in some subgroups of ISHY patients with associated risk factors and/or high central blood pressure.